Applications of emerging extracellular vesicles technologies in the treatment of inflammatory diseases - Lou, Kecheng; Luo, Hui; Jiang, Xinghua; Feng, Shangzhi (Frontiers in Immunology, 2024)
The emerging extracellular vesicles technologies is an advanced therapeutic approach showing promising potential for addressing inflammatory diseases. These techniques have been proven to have positive effects on immune modulation and antiinflammatory responses. With these advancements, a comprehensive review and update on the role of extracellular vesicles in inflammatory diseases have become timely. This review aims to summarize the research progress of extracellular vesicle technologies such as plant-derived extracellular vesicles, milk-derived extracellular vesicles, mesenchymal stem cell-derived extracellular vesicles, macrophage-derived extracellular vesicles, etc., in the treatment of inflammatory diseases. It elucidates their potential significance in regulating inflammation, promoting tissue repair, and treating diseases. The goal is to provide insights for future research in this field, fostering the application and development of extracellular vesicle technology in the treatment of inflammatory diseases.